Netflix’s Maid and representations of masculinities through social class: a textual analysis - Boehm, Melissa (Ámbitos. Revista Internacional de Comunicación, 2023)
Netflix’s Maid chronicles the struggles of a heterosexual White single mother living in the Pacific Northwest of the United States. Using the concept of hegemonic masculinities and qualitative textual analysis, this study examined the 10 episodes of the limited series Maid to document the social construction of working-class and middle-class masculinities. Sean’s dysfunctional working-class life of six packs of beer and a single-wide trailer are juxtaposed against Nate’s offer of tidy suburban middle-class comfort and safety. I argue the program reifies stereotypical portrayals of working-class and middle-class men based on their homes, jobs, family background, leisure activities, and use of alcohol and drugs. Sean does not respect Alex’s bodily autonomy, her need for financial independence, or her need for freedom from emotional abuse. Similarly, Nate is unable to see past his entitlement toward Alex based on the material benefits he offers her like a reliable loaner vehicle, a clean two-story home, and pony rides for her daughter. I contend that Alex, the main protagonist, contests hegemonic masculinities to create her own space in the world without limitations dictated by the men in her life. Documenting how Maid tells the story of a woman and her romantic partners oppressed by hegemonic masculinities can provide insight into commonsense notions of romantic partnerships in the United States today.